Teams That Teach and Learn using Steered Module in Civil Engineering Courses (TELUS MOD): An Overview - Mohammad Amirulkhairi, Zubir; Azlina, Ismail; Siti Fatimah, Che Osmi (2013)
Learning style of Malaysian civil engineering students appear to be too dependent on lecture contact hours. They do not realize that in actual almost 70% of the notional learning hours should be students own individual learning hours. Still, very few students learn individually but yet it is hard to ascertain this claim. Therefore, this paper presents an overview on team learning method where steered modules are introduced with aims to help students in appreciating their individual learning hours. This method brings in the team that learns and teaches each other without supervision from instructors. This paper found that team-learning method would benefit students in varying ways.